Rheumatoid arthritis and the risk of chronic kidney diseases: a Mendelian randomization study - Jiang, Zhaoyu; Chen, Lin; Liu, Aihui; Qi, Jiaping; Wang, Jing; Li, Yixuan; Jiang, Huan; Zhang, Ju; Huang, Shan; Mao, Chengliang; Ying, Zhenhua (Frontiers in Medicine, 2024)
The extra-articular lesions of rheumatoid arthritis (RA) are reported to involve multiple organs and systems throughout the body, including the heart, kidneys, liver, and lungs.This study assessed the potential causal relationship between RA and the risk of chronic kidney diseases(CKDs)with the Mendelian randomization (MR) analysis. Method: Independent genetic instruments related to RA and CKD or CKD subtypes at the genome-wide significant level were chosen from the publicly shared summary-level data of genome-wide association studies (GWAS).Then,we obtained some single-nucleotide polymorphisms (SNPs) as instrumental variables(IVs), which have relationship with RA in individuals of European with genome-wide significant statistical significance(p<5×10 -8 ). The inverse-variance weighting (IVW) was the main analysis method in MR analysis . Weighted median, MR-Egger , simple mode and weighted mode were conducted as supplementary sensitivity analyses. Furthermore,the levels of pleiotropy and heterogeneity are assessed by using Cochran's Q test and Leave-one-out analysis . Additionally,the relevant datasets were obtained from the Open GWAS database.Results By using IVW,main method in MR analysis ,the results showed that genetically determined RA was associated with higher risks of CKD [odds ratio (OR): 1.22, 95% confidence interval (CI) 1.13-1.31; p < 0.001] and glomerulonephritis (OR: 1.23, 95% CI 1.15-1.31; p＜ 0.000),amyloidosis (OR=1.43,95% CI 1.10-1.88, p<0.001) and renal failure (OR=1.18,95% CI 1.00-1.38, p<0.001). Then, using multiple MR methods, it was confirmed that the associations persisted in sensitivity analyses, and no pleiotropy was detected.Conclusion The findings revealed a causal relationship between RA and CKD, and including glomerularnephritis, amyloidosis and renal failure. Thus, RA patients should pay more attention to monitor kidney function to provide the opportunity for earlier intervention and lower the risk of progression to CKDs.